Abstract 111: Woven Endo Bridge‐Coil Embolization of a Middle Cerebral Artery Bifurcation Aneurysm with Secondary Lobule - Ali Alsarah; Rashid Ahmed; Adam Dmytriw; Omer Doron; Christopher Stapleton; Robert Regenhardt; Aman Patel (Stroke: Vascular and Interventional Neurology)
Introduction 18‐36% of all intracranial aneurysms are middle cerebral artery(MCA) bifurcation aneurysms. While some are much higher risk than others, they have an overall low estimated annual rupture rate of 0.36%.(1) MCA bifurcation aneurysms have been historically challenging to treat endovascularly given they often have complex morphology and wide necks. The Woven EndoBridge (WEB) is an ellipsoid embolization device designed to provide intrasaccular flow disruption along the aneurysm neck, which has been proven to be an effective method in treating a wide spectrum of wide‐necked bifurcation aneurysms. Thromboembolism and recanalization are the main concerns in treatment with the WEB device, like any aneurysm treatment approach .(2),(3) Occasionally, irregularities and secondary lobules at the base of the primary aneurysm can have persistent filling despite treatment. Methods We present a case of a right MCA bifurcation aneurysm treated by a WEB device and coil embolization. Results 48‐year‐old female with a medical history significant only for active smoking who presented with sudden onset of the worst headache of her life followed by brief loss of consciousness. No neurological evaluation was sought initially, until 2 weeks later as she continued to experience a moderate‐intensity headache associated with nausea and vomiting with frequent falls. On exam, she was alert and oriented, moving all extremities with full strength. CT head revealed an evolving acute to subacute right MCA infarction with adjacent small volume subarachnoid hemorrhage. CTA head revealed a right MCA bifurcation aneurysm measuring 6 x 6 x 7 mm with irregularity of the wall. Multifocal severe stenosis was noted in the right distal right M1 and right M2 divisions. She underwent a diagnostic subtraction angiography which confirmed an irregular right MCA bifurcation aneurysm measuring 4.3 x 4.5 x 5.7 mm (Figure 1 ‐A,B). While it was believed that the subarachnoid hemorrhage was more likely related to the recent infarct, a decision was made to treat the aneurysm given its relatively large size and irregular shape. Embolization was performed with a WEB SL 6 x 4 mm device (Figure 1: C,D ‐blue arrow). Post‐deployment angiograph showed occlusion of the aneurysm dome but persistent filling of the secondary lobule near the base of the aneurysm. Given this residual lobule filling, a decision was made to continue additional embolization with a hyper soft 3D 2 mm X 2 cm coil(Figure 1: C,D ‐ yellow arrow). Final angiography revealed complete occlusion of the aneurysm. Vasospasm of the distal M2 divisions and multiple M3 branches in the right MCA vascular territory was also noted. Therefore, she was treated with 20 mg of intra‐arterial Verapamil with improvement. She was started on Aspirin 325 mg daily. Daily transcranial dopplers were negative for vasospasm. She remained neurologically stable and was discharged home 5 days after admission ambulating independently. Conclusion With modern advances in endovascular devices, many MCA bifurcation aneurysms can be treated minimally invasively. However, there are some limitations to the WEB since every aneurysm is different and there are a finite number of sizes and shapes available for WEB. This case illustrates that adjunctive coil embolization can successfully occlude a residual secondary base lobule after WEB embolization.